2007
DOI: 10.4049/jimmunol.179.3.1803
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cross-Presentation by Heat Shock Protein 90-Peptide Complex-Loaded Dendritic Cells via an Endosomal Pathway

Abstract: It is well-established that heat shock proteins (HSPs)-peptides complexes elicit antitumor responses in prophylactic and therapeutic immunization protocols. HSPs such as gp96 and Hsp70 have been demonstrated to undergo receptor-mediated uptake by APCs with subsequent representation of the HSP-associated peptides to MHC class I molecules on APCs, facilitating efficient cross-presentation. On the contrary, despite its abundant expression among HSPs in the cytosol, the role of Hsp90 for the cross-presentation rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 36 publications
3
109
0
1
Order By: Relevance
“…Antigenic peptide-bound HSP 70 and 90 family proteins are known to work as immune modulators that enhance the cross-priming pathway and enhance antitumor immunity (44)(45)(46)(47). In this study, we confirmed anti-DNAJB8 immunity with DNAJB8-immunized mouse spleen cells.…”
Section: Discussionsupporting
confidence: 68%
“…Antigenic peptide-bound HSP 70 and 90 family proteins are known to work as immune modulators that enhance the cross-priming pathway and enhance antitumor immunity (44)(45)(46)(47). In this study, we confirmed anti-DNAJB8 immunity with DNAJB8-immunized mouse spleen cells.…”
Section: Discussionsupporting
confidence: 68%
“…As others and as we have already demonstrated, heat shock treatment accelerates the loading of peptides onto the binding sites of ORP150 and other HSPs (22). As shown in Fig.…”
Section: Generation Of Orp150-peptide Complex In Vitromentioning
confidence: 70%
“…Extracellular HSP-Ag complexes, which are released from damaged tumor cells or virusinfected cells, are considered to be candidate Ag sources for crosspresentation. The pathway for cross-presentation has been shown to be comprised of two distinct intracellular routes, a proteasome-TAP-dependent pathway and an endosome-recycling pathway (22,39). Recent reports have identified the pathway wherein peptide exchange onto recycling MHC class I molecules occurs within early endosomal compartments (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractions of tumor lysates were tested in vivo and revealed the HSPs as sought-after tumor-rejection antigens. 2,37,38 They included Gp96, 2,[38][39][40] Hsp90, 39,41 Hsc70/Hsp70 39,42,43 as well as calreticulin, 44,45 Hsp110 and Grp170. [46][47][48] In the ensuing years, these chaperones were extensively studied and successfully applied in preclinical cancer vaccination approaches (Table 1).…”
Section: Discovery Of Hsps Gp96 and Their Immunological Propertiesmentioning
confidence: 99%